THE FACTORS THAT SHAPED THE EARLY ARTISTIC TASTING OF THE ANCIENT ARABS (TAMADDUN NURI JURNALI, 2024)
The article scientifically analyzes the reasons for the emergence of Arab Jahili literature, the history of which dates back thousands of years, and the subsequent early medieval prose and poetry works in this ancient civilization, as well as the sources of the high artistic taste of the Arabs, which existed since ancient times.